THE MEANING OF BUSINESS SUSTAINABILITY IN TOURISM COMPANIES FOR PT. KUSUMA AGROWISATA, BATU CITY - Masykur, Avesiana Akhda Khilya; Orbaningsih, Dwi; Muawanah, Umi; Anwar, Anwar (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
The principle of sustainability in business is often overlooked, with companies focusing solely on profit without considering the social and environmental impacts. However, it is a known fact that companies will be able to operate for a longer period of time if they pay attention to social and environmental aspects without neglecting the profit aspect. Similarly, tourism companies are inseparable from these three aspects: social, environmental, and profit. One company that researchers found has begun implementing sustainable business principles is PT. Kusuma Agrowisata Kota Batu, a company located in a city known as a tourist city. As explained above, this study aims to improve the understanding of the meaning of sustainable business, especially in tourism companies, for stakeholders, so they can act properly and correctly in all company activities. This study uses a phenomenological approach to generate accurate meanings for eight respondents: one person from within the company, one from the government, three from the local community, and three from tourists. The results of this study obtained five meanings of sustainable business through an in-depth interview process based on the experiences of the respondents of this study. Namely sustainable business is a form of long-term benefits, empowered and independent, educational and environmentally friendly, a form of commitment to social, and a form of cultural preservation in business innovation.